Evaluation of a New Rapid Quantitative D-dimer Assay in Patients with Clinically Suspected Deep Vein Thrombosis - D’Angelo, Armando; D’Alessandro, Gabriella; Tomassini, Loredana; Pittet, Jean Louis; Dupuy, G; Crippa, Luciano (Thrombosis and Haemostasis, 1996)
The sensitivity and specificity for deep vein thrombosis (DVT) of a new rapid, quantitative and precise (total imprecision < 10%) D-dimer assay suitable for individual measurements (VIDAS D-DIMER, bio-Merieux, France) were evaluated in a consecutive series of 103 in- and out-patients submitted to serial compression ultrasonography (C-US) for the clinical suspicion of DVT (n = 66) or of DVT recurrence (n = 37) and symptoms lasting from 1 to 15 days. DVT was found in 22 patients at baseline testing and no patient with an initially negative C-US developed vein incompressibility at follow up. The time elapsed from the onset of symptoms was negatively associated with D-dimer levels both in patients with and in those without DVT. In the entire series of patients, the sensitivity of a positive D-dimer test (≥1.0 Μg/ml) for the presence of DVT was 96% (21/22 patients, 95% confidence interval 75-100%) with a specificity of 75% (64-84%), a negative predictive value of 98% (90-100%), a positive predictive value of 51% (35-67%), and an overall accuracy of 80% (70-87%). A normal D-dimer value (0.22 Μg/ml) was observed in one patient with DVT and symptoms lasting from 15 days. The approach of withholding C-US testing in patients with symptoms lasting from less than 11 days and D-dimer levels below the cut-off value was compared to serial C-US testing alone in a cost-effectiveness analysis subdividing the 66 patients with a first episode according to their clinical pretest probability of DVT. Thrombosis was detected in 6.7% of the patients in the low probability group (n = 15), 16.7% of the patients in the moderate probability group (n = 24), 51.9% of the patients in the high probability group (n = 27) and 8.1% of patients with suspected DVT recurrence. Calculated cost-savings for each DVT diagnosed ranged from 5% in the high pretest probability group to 55% in the low pretest probability group and to 77% in patients with suspected DVT recurrence.The safety of avoiding C-US testing in symptomatic patients with a negative D-dimer test should be evaluated in clinical management studies.